Randomized clinical trial to evaluate the effectiveness of different thicknesses of stabilization splints in treating temporomandibular disorder using joint vibration analysis as a novel diagnostic tool - Jyoti Sharma; Rajlakshmi Banerjee; Vijeta Gajbhiye; Anushree Bhoge; Priti Jaiswal; Kiran Nayak (The Journal of Indian Prosthodontic Society)
Aim: The purpose of the study was to comparatively evaluate temporomandibular joint function and treatment response using joint vibration analysis (JVA) in patients exhibiting disc displacement with reduction (DDR), treated with three variable thickness of stabilization splints. JVA analyzed these vibrations to detect internal joint abnormalities, and their patterns were further categorized using the Piper classification was highly accurate and hence used over magnetic resonance imaging. Settings and Design: Randomized clinical trial. Materials and Methods: The splint of different thicknesses, i.e., Group A (3 mm), Group B (4 mm), and Group C (5 mm) were given to the study participants for 10 week interval, and pre and posttreatment efficacy was recorded using JVA. Stress perseverance and tooth wear index were recorded with a pre and postquestionnaire. Statistical Analysis Used: The one way analysis of variance f test and Turkey’s post hoc test for multiple comparisons were used to statistically assess the results. Results: The treatment response with Group A and B thickness of stabilization splints was significant (P = 0.01) and with Group C was not significant (P = 5.28). The statistical result of stress perseverance was not significant between the three groups, although reflecting female participants were affected more. The tooth wear index was significant with all the three groups (P = 0.09). Conclusion: The study concluded that the splints given to Group A and Group B showed effective treatment response, while Group C showed positive response in a few individuals, but some individuals compliant of discomfort. The stress level was high in female individuals. Among all the participants, the concern of tooth wear was present.